2015
DOI: 10.1080/07929978.2014.958392
|View full text |Cite
|
Sign up to set email alerts
|

Pod and seed defensive coloration (camouflage and mimicry) in the genus Pisum

Abstract: The small genusPisumis composed of two annual species,P.fulvumand the domesticated peaP.sativum. The domesticated pea has two main wild-type taxa:P.elatiusandP.humile. Members of the genusPisumare not well defended from herbivory by high levels of toxins like the seeds of many other legume species. We studied the color patterns in the pods and seeds of these three wild taxa (P.fulvum,P.elatiusandP.humile) in order to examine their potential for defensive coloration (camouflage and Batesian mimicry). All three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 65 publications
0
9
0
Order By: Relevance
“…It is interesting that while the young partly transparent pods of Lathyrus ochrus, Pisum elatius and P. humile seem to mimic caterpillars because they are partly transparent (e.g., Fig. 1), when these pods are more mature and no longer transparent, they mimic aposematic caterpillars by expressing a line of very conspicuous red spots (see 24,25 ; and Fig. 3).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is interesting that while the young partly transparent pods of Lathyrus ochrus, Pisum elatius and P. humile seem to mimic caterpillars because they are partly transparent (e.g., Fig. 1), when these pods are more mature and no longer transparent, they mimic aposematic caterpillars by expressing a line of very conspicuous red spots (see 24,25 ; and Fig. 3).…”
Section: Resultsmentioning
confidence: 99%
“…A detailed analysis of defensive pod and seed coloration in the 3 Mediterranean Pisum species showed that many individuals of 2 of them (Pisum elatius and P. humile) visually mimic aposematic caterpillars. 25 Interestingly, aposematic caterpillar mimicry is also performed by nestlings of the Amazonian birds Laniocera hypopyrra and Laniisoma elegans in order to reduce predation. 26,27 Caterpillar mimicry as defense from herbivory is part of a larger phenomenon of visual, e.g., 24,25,[28][29][30][31][32] and chemical 33 animal mimicry as defense from herbivory.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aposematism has been proposed to operate in poisonous seeds (Cook et al, 1971;Wiens, 1978;Harborne, 1982), flowers (Hinton, 1973;LevYadun, 2009), fruits (Hill, 2006;Lev-Yadun, 2009), leaves (LevYadun and Gould, 2007Archetti, 2009a;Archetti et al, 2009), and thorny plants (Lev-Yadun, 2001, 2003a,b, 2006aNe'eman, 2004, 2006;Rubino and McCarthy, 2004;Ruxton et al, 2004;Speed and Ruxton, 2005;Halpern et al, 2007a, b;Gould, 2007, 2009;Lev-Yadun and Halpern, 2008). Other types of defensive coloration include mimicry of butterfly eggs (Shapiro, 1981a,b;Williams and Gilbert, 1981), mimicry of dead leaves (Stone, 1979), mimicry of ants, aphids, poisonous caterpillars (Lev-Yadun and Inbar, 2002), of spider webs (Yamazaki and Lev-Yadun, 2015), of thorns (Lev-Yadun, 2003a), of leaf-mining insects (Smith, 1986;Soltau et al, 2009), delayed greening to diminish (and probably also signal) nutritive value (Kursar and Coley, 1992), undermining of herbivorous insect camouflage Lev-Yadun, 2006aLevYadun andGould, 2007, 2009), variegation and coloration as camouflage (Wiens, 1978;Givnish, 1990;Lev-Yadun, 2006b;Fadzly et al, 2009;Niu et al, 2014;Aviezer and Lev-Yadun, 2015), and variegation that someho...…”
Section: Ecological Defensesmentioning
confidence: 99%
“…I was painfully wounded by such spring actions numerous times during field work and fully appreciate their nasty reaction. Plants also use camouflage, [38][39][40][41][42][43][44][45] and pathogenic bacteria that they insert into the tissues of herbivores, 46 they undermine the camouflage of herbivorous insects, 47 and also use strong windinduced leaf movements to get rid of herbivores, 48,49 all of these in order to defend themselves from herbivory. Plants have many other types of mechanical defenses 30,50,51 including even anisotropic arrangement of structural defenses that can lead invertebrate herbivores away from the plants.…”
mentioning
confidence: 99%